The Relationship between Teachers’ Perceptions on The School Director’s Leadership Style and The School’s Organizational Climate at Assumption College English Program, Bang Rak, Bangkok, Thailand - Josaphat, Saw; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2016)
The purpose of the study was to identify the relationship between teachers’ perceptions on the school director’s leadership style and the school’s organizational climate at Assumption College English Program, Bang Rak, and Bangkok, Thailand. The research objectives of the study were: (1) to identify the teachers’ demographics at Assumption College English Program, Bang Rak, Bangkok, Thailand, (2) to identify the teachers’ perceptions on the school director’s leadership style at Assumption College English Program, Bang Rak, and Bangkok, Thailand. (3) to identify the teachers’ perceptions on the school’s organizational climate at Assumption College English Program, Bang Rak, Bangkok, Thailand. (4) to determine the relationship between teachers’ perception on the school director’s leadership style and the school’s organizational climate at Assumption College English Program, Bang Rak, Bangkok, Thailand. The study was based on the theoretical support from transformational leadership and school’s organizational climate. There were three parts in the questionnaire. They are teachers’ demographics, school director’s leadership style and school organizational climate survey. 94% of the distributed questionnaire was returned. It was analyzed by percentage, frequency, mean, standard deviation and Pearson’s Product Moment Correlation Coefficient. The study found that the overall level of school director’s leadership style was high according to the research finding based on five-point Likert scale. Each dimension of the level of school director’s leadership style was High, the level of the school’s organizational climate was High, and there was a significant relationship between the teachers’ perception on the school director’s leadership style and the school’s organizational climate at Assumption College English Program, Bang Rak, Bangkok, Thailand. Both the school director and the departmental heads are recommended to emphasize the development of school organizational climate and transformational leadership style more, because according to the research findings, the areas of intelligent stimulation in transformational leadership and milieu in organizational climate were a bit low.